Diffusion of nitrogen gas through polyethylene based films. Issue 6 (25th August 2021) - Visco, Annamaria; Scolaro, Cristina; Torrisi, Alfio; Torrisi, Lorenzo
Abstract: Polyethylene‐based films can be used as sealant materials at room temperature in packaging applications. They can be also melted and sealed with glass, acting as sealant material in solar cells. The polyethylene‐based polymers investigated in this paper are a linear low‐density polyethylene modified with maleic anhydride (or PE‐MAH), and an ethylene acrylic acid copolymer (or EMAA). Measurements of nitrogen gas diffusion coefficient (D) have been performed at three different temperatures ranging between 23°C and 32°C. The experimental apparatus used to measure the diffusion coefficients is original compared with other commonly used. The obtained D results have been correlated with the polymeric structure and morphology by means of differential scanning calorimetry (DSC), thermogravimetric‐analyses (TGA), X‐ray diffraction (XRD), and scanning electron microscopy (SEM) experimental analyses. Furthermore, D‐coefficients are compared with the literature data of other polyethylenes with different structural organization (HDPE, LLDPE, and LDPE). The thermal activation energy is evaluated for the two polymers. Arrhenius plot has been used to calculate the activation energies of both polymers and to predict the D‐coefficient at other temperatures, close to these analyzed. Abstract : The permeability to nitrogen gas in two polyethylene‐based films (named PE‐MAH and EMAA) was evaluated by original equipment. The diffusion data were correlated to their different structure and macromolecular morphology by means of different characterization tests. The experimental results have shown that PE‐MAH has a much lower gas permeability (due to its smaller free volume) and greater thermal stability (thanks to its higher crystalline order and lamellar thickness) than EMAA.